SUBCELLULAR-LOCALIZATION OF RADIOACTIVELY LABELED DEFIBROTIDE IN CULTURED ENDOTHELIAL-CELLS - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1992)
Defibrotide is a new antithrombotic and fibrinolytic drug which is obtained by controlled depolymerization of mammalian DNA. In various models of arterial and venous thrombosis, it has been shown that it induces tissue plasminogen activator [tPA] and prostacyclin [PGI2] release from the vessel wall. We have previously shown the presence of specific binding sites with a K(d) of 4.2-mu-g/ml for radioactively labelled defibrotide. The present study was undertaken to identify the location of the binding site. Confluent cultures of endothelial cells from human umbilical vein were incubated with media containing H-3-acetyl-defibrotide for various intervals of time. Cells were then washed and harvested nonenzymatically. Subcellular location of H-3-defibrotide was investigated by fractionating cells on discontinous sucrose gradient and measuring the distribution of radioactivity. 5'-nucleotidase enzyme activity was also measured to ensure the location of membrane fraction Our results suggest that the major location of H-3-defibrotide in endothelial cells is the plasma membrane. On the other hand, nuclei also contain a considerable amount of the drug which suggests a mechanism where binding to a membrane protein is followed by internalization.
Keywords: ENDOTHELIAL CELLS; DEFIBROTIDE; SUBCELLULAR LOCALIZATION